The Implementation of Constructivism Learning in Islamic Religious Subject At Senior High School Plus Bina Insani - Sari, Oktavita (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
Constructivism approach in teaching and learning is based on a synthesis of several research in cognitive psychology and social psychology, as well as techniques of operant conditioning theory in behavioral psychology. The basic premise is that individuals must actively "build" their knowledge and skills (Brunner, 1990) from information obtained in the process of building a learning framework from the environment outside. Teachers will not be able to give all knowledge to their students. Students must construct knowledge in their own minds. The essence of constructivism theory is 'ideas'. Students must find and transform complex information into other situations. With that basis, teaching and learning process must be designed into a process of 'constructing' rather than 'receiving' knowledgePendekatan konstruktivisme dalam belajar dan pembelajaran didasarkan pada perpaduan antara beberapa penelitian dalam psikologi kognitif dan psikologi sosial, sebagaimana teknik-teknik dalam modifikasi perilaku yang didasarkan pada teori operant conditioning dalam psikologi behavioral. Premis dasarnya adalah bahwa individu harus secara aktif “membangun” pengetahuan dan keterampilannya (Brunner, 1990) dari informasi yang diperoleh dalam proses membangun kerangka belajar dari lingkungan luar dirinya.Guru tidak akan mampu memberikan semua pegetahuan kepada siswanya. Siswa harus mengkonstruksikan pengetahuan dibenak mereka sendiri. Esensi dari teori konstruktivisme adalah ’ide’.  Siswa harus menemukan dan mentransformasikan suatu informasi kompleks ke situasi lain. Dengan dasar itu, maka belajar dan pembelajaran harus dikemas menjadi proses ‘mengkonstruksi’ bukan ‘menerima’ pengetahuan.